Sense of Belonging and Suicide: A Systematic Review. (July 2013) - Hatcher, Simon; Stubbersfield, Olivia
Objective: To systematically review the research on the association between sense of belonging and suicide. Method: We systematically reviewed electronic databases for studies that included assessments of suicidality and belonging. Results: We found 16 studies that met our eligibility criteria. They all found an association between belonging and suicidality but nearly all of the studies were in nonclinical populations, and the association was weak and could be taken into account by confounding factors. Conclusions: Low sense of belonging has a weak association with suicidality. However, current concepts make it hard to distinguish from loneliness or other measures of social support. An alternative view of belongingness, as a sense of connectedness to things other than people and in the past as well as the present, may generate alternative ideas about useful clinical interventions that may be especially relevant to indigenous populations.